METODE ROSULULLAH SAW TENTANG PENGAJARAN AKHLAQ DALAM KITAB SHAHIH AL-BUKHORI - Hadi, Abdul (TA'LIMUNA: Jurnal Pendidikan Islam, 2013)
At-Thariiqah Ahammu minal Maadah “the method is more important than subject material”, it’s arabic idion which made consdering of important methodology in Islamic education and da’wah. The success of Rosulullah (peace be upan him), in regard to guide his mankind from evil to the light of Islam. Eventhough of his vision from the great Allah who couldn’t separated by his implementation. The conclusion of it tells that Rosulullah uses the variation methods in moral perspective to his sahabah. The whole methods of Nabee (peace be upon him) is: a) Al Hikmah indicates of his softening attitude and distncton to everybody, b) Al Mau’izah is about advice, exhoration, speech, stories, and tamtsil (fale story), c) Al Hiwar or Jidal (dialogue or debate), d) Qudwah (model), e) Targhib (motivaton), this type can be tabsyir (good news) by heaven and the mercy of Allah or blessed from the punishment in here after (akhirat), g) Al-Hajr (to isolate), h) Taubikh (disgrace), i) Ta’qib, phisic punishment (hudud) such as sexual act, Liwath (homosexual), Qishash (homocide), j) Talwih (allegory or satire), k) Ta’wid (custom), l) Taddaruj/gradual (phase), m) Rihlah (travelling for wordly goals, such as businees, own property way of for Tarfiyah (recreation or holiday plan or or entertain) or spiritual way, include hijrah (migration), hajj and umroh, jihad fi sabilillah or silaturhcem.